Penerapan Logika Matematika dalam Menyelesaikan Masalah Sehari-hari (Asosiasi Riset Ilmu Matematika dan Sains Indonesia, 2025)
Mathematical logic is a branch of science that studies the principles of logical reasoning and how to judge the truth of a statement. This article discusses the role of mathematical logic in everyday life, especially in education, technology, and finance. Mathematical logic has been proven to help improve critical, analytical, and systematic thinking skills, making it easier for individuals to solve various problems more effectively and efficiently. In the world of education, mathematical logic supports the development of rational, argumentative, and problem-solving skills, and is an important foundation in the science and mathematics curriculum. Teachers can leverage this logic to encourage students in building consistent reasoning and logical argumentation. In the field of technology, mathematical logic is the foundation in the development of modern computing systems, such as algorithms, programming, artificial intelligence, and data structures. Without mathematical logic, digital systems such as search engines, software, and applications cannot function optimally. In finance, mathematical logic plays a role in budget strategy, investment decision-making, statistical analysis, and rational risk management. With a good understanding of logic, individuals and institutions can make more wise and measurable financial decisions. Although his contribution is large, there are still many people who do not understand the basic concepts of mathematical logic. This can be overcome through more inclusive education, contextual approaches, and interactive learning based on real problems, both in schools and non-formal environments. This study emphasizes the importance of mathematical logic as a foundation in supporting a more rational, efficient, and structured life in today's modern era. Increasing mathematical logic literacy can be a national strategy to create a society that thinks critically, is competitive, and ready to face global challenges.